A highly active and recyclable catalyst for the synthesis of indole and phenyl ether. Issue 113 (2nd November 2015) - Qiao, Bo; Zhang, Le; Li, Rong
Abstract : A new simple catalytic system consisting of copper-aluminium and hydrotalcite (CuAl–HT) has been developed using a facile one-pot method without harm to the environment. Abstract : A new simple catalytic system consisting of copper-aluminium and hydrotalcite (CuAl–HT) has been developed using a facile one-pot method without harm to the environment. The catalyst was characterized using TEM, XRD and XPS. It could be used as an efficient catalyst for the synthesis of both indole and phenyl ether. As expected, the catalyst afforded high catalytic activity for the selective synthesis of indole via intramolecular dehydrogenative N-heterocyclization of 2-(2-aminophenyl)ethanol. Meanwhile, it also exhibited superior catalytic properties for an Ullmann-type coupling reaction to synthesise phenyl ether from iodobenzene and phenol. The CuAl–HT catalyst showed higher activity than conventional catalysts based on copper and could be recycled several times with stable catalytic activity. This procedure has real economic advantages since no expensive materials were used.